TOWARD CRITICAL EDUCATIONAL TECHNOLOGY FOR EARLY CHILDHOOD EDUCATION - Subkhan, Edi (Indonesian Journal of Early Childhood Education Studies, 2013)
This article as a theoretical overview explains and introduces the basic concept of the critical perspective on educational technology for early childhood education, especially for the Indonesian audience. The critical perspective derived from the critical pedagogy notions is very important as a critical tool of analysis on examines the creating, using, and managing of the learning media and method for early childhood education. The critical analysis result would be the prominent consideration on educational technology activities (creating, using, managing) and the critical pedagogy notions itself become the reference paradigm and foundation for those activities. The subtantial objectives of the early childhood education from the critical pedagogy perspective are tend to bring the learning practice more democratic, emancipatory, dialogic, participatory, andtransformative for the childs cognitive, afective and psychomotoric development. The concern of the critical pedagogy for early childhood education is not insist to build the childs critical consciousness, but to nurture the childs need for critical inquiry, in this case the teachers position is important to develop and practicing the learning practice based on the critical pedagogy notions and also examine critically the early childhood education policy, its curriculum, and etc.